Pendekatan pengurusan stres berdasarkan konsep al-Nafs: Kajian terhadap ayat-ayat al Qur’an terpilih / Siti Hasmah Muhamad Don - Siti Hasmah , Muhamad Don (2022)
Stress needs to be managed properly, otherwise, it can have adverse effects on individual health and also behavioral problems. There have been various stress management approaches applied in the West and Islam. The West, for example, uses many psychological approaches in managing stress. From the Islamic point of view, the stress management approach is derived from the Qur’an and hadith instructions. This study focuses on the stress management approach according to Islam which is based on the concept of al-nafs as highlighted in the Qur’an. A review of the previous literature has shown that studies on the Qur’an have succeeded in forming the concept of al-nafs (psyche) which is an important element in human beings. From this concept, various approaches on stress management according to Islam were formed, which were highlighted by the earlier and contemporary scholars. However, it is found that the stress management approach that leads to the concept of al-nafs itself is still less discussed, especially in the context of textual studies of the relevant Qur’anic verses. Therefore, this research highlights the stress management approach based on the concept of al-nafs by focusing on the study of the selected Qur’anic verses. This study is based on a qualitative method that used document analysis and content analysis. Findings of the study indicated that al-nafs system of the humans greatly influences the formation of behavior, including stress-related behaviors. This study also found that there are no specific Qur’anic verses that directly mentions stress management approach instead of it provides general indication. Thus, textual study of the relevant Qur’anic verses related to the context of al-nafs is pertinent for the community to embrace a more holistic stress management approach.